∝ + β = π / 2 and ∝ = β + Γ
then prove
1) tan ∝ = tan β + 2 tan Γ
2) tan∝.tanβ = 1
Answers
Answered by
1
Answer:
1) tan ∝ = tan β + 2 tan Γ
2) tan∝.tanβ = 1
Step-by-step explanation:
2) ∝ + β = π / 2
β = π / 2 - ∝
tan β = tan ( π / 2 - ∝)
tan β = cot ∝
tan β = 1 / tan ∝
tan β . tan ∝ = 1
1) ∝ = β + Γ
∝ - β = Γ
tan (∝ - β) = tan Γ
tan ∝ - tan β / 1 + tan∝.tan.β = tanΓ
tan ∝ - tan β = tan Γ (1 + tan∝.tan.β)
tan ∝ - tan β = tan Γ (1 + 1)
tan ∝ - tan β = 2tan Γ
tan ∝ = 2tan Γ + tan β
Hence Proved
Please Mark My Answer As Brainliest
⊕Thank You ⊕
Similar questions
Hindi,
2 months ago
Hindi,
2 months ago
English,
4 months ago
Math,
11 months ago
World Languages,
11 months ago